EFFECT OF EGR ON COMBUSTION AND EMISSION CHARACTERISTICS IN DIESEL BIOETHANOL DUAL-FUEL ENGINE - Teoh, Yew Heng; How, Heoy Geok; Balakrishnan Navaneetha, Krishnan; Hishammudin Afifi, Huspi (Penerbit UTM Pres, 2022)
The diminution of global fossil fuel reserves is a main concern and alternative fuel sources are needed to tackle the issue of global warming caused by greenhouse gases. Biofuels have been considered as an alternative to the depleting oil resources. This study investigates the effect of exhaust gas recirculation (EGR) on combustion, performance and emission characteristics in a single-cylinder reactivity-controlled compression ignition engine using diesel-bioethanol as fuel. A dual-fueling strategy is achieved such that bioethanol is introduced into the intake manifold using a port-fuel injector (PFI) while diesel is directly injected into the combustion chamber. Various percentage of EGR rate were considered and compared. The important parameters that were taken into consideration are: engine efficiency, combustion characteristics, and exhaust gas emissions. Experimental results revealed that the EGR variation had a noticeable effect on the engine performance, emissions, and combustion characteristics with diesel-bioethanol dual fuel operation. Introduction of EGR has effectively reduced the combustion pressure rise rate along with keeping the NOx emission within the legislation norm. Besides, the results also revealed that the diesel-bioethanol dual fuel combustion has low smoke emission across all EGR ratios. Lastly, the results showed that the engine operating under diesel-bioethanol fueling could achieve high efficiency with near zero nitrogen oxides (NOx) and smoke emissions.